An Empirical Investigation of the Relationship Between Spirituality, Work Culture, and Burnout: The Need for an Extended Health and Disease Model - Listopad, Ian W.; Esch, Tobias; Michaelsen, Maren M. (Frontiers in Psychology, 2021)
Apart from biological, psychological, and social factors, recent studies indicate that spirituality and work culture also play an important role in the onset of burnout. Hence, the commonly applied bio-psycho-social model of health and disease might not be sufficient to explain and describe burnout comprehensively. This study investigates empirically the relationship between spirituality (operationalized by perceived meaningfulness of work) and work culture (operationalized by sense of homeliness of the working environment) with burnout risk and work engagement. For this purpose, an anonymous cross-sectional data collection with fully standardized questionnaires and selected socio-demographic and work-related items was conducted among working adults from different industries (N = 439) via social media and local health service centers. For all scales and subscales, we found significant moderate to strong correlations. Furthermore, positive meaning within the perceived meaningfulness of work scale was the largest beta coefficient for burnout (β = –.65) and work engagement (β = .62). Within sense of homeliness, the largest beta coefficient for burnout was needs fulfillment (β = –.34) and for work engagement emotional connection (β = .36). The strong associations suggest that the current health and disease model needs to be expanded to a bio-psycho-socio-spirito-cultural model in order to be able to sufficiently describe burnout. Perceived meaningfulness of work and sense of homeliness should be adequately considered when examining the onset of burnout, describing burnout as a concept, and explain work engagement.